2013
DOI: 10.17265/1537-1514/2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Concentration, Intellectual Capital, and Firm Performance: Evidence From Italy

Abstract: The paper extends previous research on the topic of intellectual capital (IC) and the relationship between ownership concentration (OC) and firm performance. The ambitious goal of this work is to answer three questions: (1) Whether there is a relationship between IC and firm performance; (2) Whether there is a relationship between the efficiency of IC and the ownership structure of the Italian listed companies; and (3) If the performance of Italian listed companies is influenced by the ownership structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Jensen and Meckling (1976) provided a theory about this, which is called agency theory. Prior studies explored the significant association between IC and OS (Al-Sartawi 2018; Celenza and Rossi 2013;Nassar et al 2018).…”
Section: Ownership Structure and Intellectual Capitalmentioning
confidence: 99%
“…Jensen and Meckling (1976) provided a theory about this, which is called agency theory. Prior studies explored the significant association between IC and OS (Al-Sartawi 2018; Celenza and Rossi 2013;Nassar et al 2018).…”
Section: Ownership Structure and Intellectual Capitalmentioning
confidence: 99%
“…However, some other studies showed the reverse results. Moreover, the CEE declined the firm's ROA [13,48,49] and ROE [13,50] and market performance (TQ) [51]. The influence of CEE on corporate performance is evident in various directions.…”
Section: Capital Employed Efficiency (Cee) and Companies' Performancementioning
confidence: 99%